BELIEFS AND RELIGIOUS PRACTICES OF AFRICAN BACKGROUND PRESENT IN BAHIA HONDA (PINAR DEL RÍO) - Basso, Silfredo Rodríguez (Universidad Autónoma Indígena de México, 2018)
The present article is part of PhD thesis about the presence of the African legacy in the cultural identity of Bahia Honda, former municipality of Pinar del Rio province, Cuba until December 2010. With the systematization of the main beliefs and practices of this existent substratum (Santería, Palo Monte y Arará Magino), each component are analyzed based on a socio- cultural approach as an integrated part as the cultural identity in the province. Apart from “spiritism”, an expression that crosses and integrates the different religious manifestations, the main conclusion we could arrive in this work consists on the present specific peculiarities that have converted the religious in a representative universe of the cultural identity of this location in Pinar del Rio.